Strategi Hubungan Masyarakat Lembaga Penyiaran Publik Televisi Republik Indonesia Jambi dalam Mempromosikan Program Acara - Nopita Sari; Mila Wahyuni; Eka M. Taufani (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This research is motivated by a phenomenon that occurs in the field of Public Relations (HUMAS) of the Republic of Indonesia Television Public Broadcasting Institution (LPP TVRI) Jambi. A strategy is needed by TVRI Jambi as times change where the interest of television viewers is decreasing due to competition from both private television and new media. The audience follows a style that has value. Therefore it is necessary to have a Public Relations in order to expand public knowledge about what programs exist at TVRI in order to increase the existence of TVRI Jambi. This study uses a qualitative method with a case study approach. Data collection methods used in the form of observation, documentation, and interviews with data analysis techniques, namely data reduction, data presentation, and data verification. The results of this study the authors found that the Public Relations Strategy in promoting TVRI Jambi programs to improve the quality of TVRI programs in the eyes of the public to better understand and know broadcasts on TVRI Jambi therefore Public Relations itself uses a communication strategy Public relations strategy, communication, advertising , sales promotion, publicity , corporate design The problems of Public Relations in promoting LPP TVRI programs in Jambi, weak human resources, PR efforts in promoting LPP TVRI Jambi programs in collaborating with other agencies.